Anomalous Amplitude Attenuation Method to Enhance Seismic Resolution - Muchlis . (Journal of Aceh Physics Society, 2015)
Anomalous Amplitude Attenuation (AAA) is a method to process seismic data with multilevel processing (multi step flow). AAA is indicated for identifying anomalous seismic amplitude (amplitude noise) such as: spike noise, noise and noised trace. AAA is a filter applied to the data in the frequency domain, range, both in CMP/CDP, offset or gather shot. Processing of the data depends on how the sensor (the geophone) receives seismic waves, and then set the data back into the format demultiplex (SEG-Y) and then processed according to the rules (flowchart) seismic reflection processing.This method has been applied to improve the old seismic data of an exploration company in prospecting the unseen structure in prospecting the hydrocarbon trapped within sedimentary rock subsurface.